Thickness of Buccal and Lingual Alveolar Bone Plates According to the Position of Impacted Mandibular Third Molars on Cone-Beam Computed Tomography Scans - Seyed Alireza Parhiz; Pegah Bakhtiary; Farzaneh Mosavat; Mohammad Javad Kharazi Fard (Tehran University of Medical Sciences, 2019)
Objectives: This study sought to assess the thickness of buccal and lingual alveolar bone plates according to the position of impacted mandibular third molars on cone-beam computed tomography (CBCT) scans. Materials and Methods: Eighty-four CBCT scans of impacted mandibular third molars were evaluated in this retrospective study. All images had been obtained by ProMax 3D CBCT system with the exposure settings of 78 kVp, 12 mA, 16 s time, 0.2 mm voxel size and 10 × 9 cm field of view. The impaction angle of teeth and the thickness of buccal and lingual cortical plates were determined on images by drawing lines in the anterior, middle, posterior, superior, central and inferior regions. Thickness of bone plates was analyzed according to the position of impacted molars relative to the buccal and lingual plates using the Student t-test and relative to the second molars using one-way ANOVA and Tukey's test. Results: In the buccolingual direction, the buccal plate thickness was maximum in lingual position followed by central position, and minimum in buccal position of the teeth. The lingual plate thickness was minimum in horizontal and distoangular positions and maximum in the mesioangular position of impacted teeth. Conclusion: Risk of lingual plate preformation is higher in surgical removal of impacted third molars with distoangular and horizontal positions. Thus, further attention must be paid by the surgeons to such cases.